Biological treatments for temporomandibular joint disc disorders: strategies in tissue engineering - Trindade, Daniela (2022)
The temporomandibular joint (TMJ) is an important structure for the masticatory systemand the pathologies associated with it affect a large part of the population and impair people’slifestyle. It comprises an articular disc, that presents low regeneration capacities and the existingclinical options for repairing it are not effective. This way, it is imperative to achieve a permanentsolution to guarantee a good quality of life for people who suffer from these pathologies. Completeknowledge of the unique characteristics of the disc will make it easier to achieve a successful tissueengineering (TE) construct. Thus, the search for an effective, safe and lasting solution has alreadystarted, including materials that replace the disc, is currently growing. The search for a solutionbased on TE approaches, which involve regenerating the disc. The present work revises the TMJ disccharacteristics and its associated diseases. The different materials used for a total disc replacementare presented, highlighting the TE area. A special focus on future trends in the field and part of thesolution for the TMJ problems described in this review will involve the development of a promisingengineered disc approach through the use of decellularized extracellular matrices.